Politik Pendidikan Tentang Kebijakan Full Day School (Analisis Karakter Kebijakan Publik) - Muhammad Chabibi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
Human development planning through government policy is a very important thing and needs to be considered in order to form a qualified Human Resources. Regulation of the Minister of Education and Culture No. 23 of 2017 About Full Day School is a program intended for teachers, students, education personnel and school organizers to prepare learners in the era of globalization through the restoration of character education in schools. This paper discusses human development planning through PERMENDIKBUD No. 23 of 2017 by policy actors with the perspective of policy character (Responsive, Orthodox, Paternalist). With the descriptive analysis method, this paper concludes that the policy of Full Day School is a policy of orthodox character to override the participation and public interest in the policy so that the consequences are rejection from different education observers even contrary to the public interest.